A Class of Fully Nonlinear Equations Arising in Conformal Geometry. (9th October 2020) - Chen, Li; Guo, Xi; He, Yan
Abstract: In this paper, we consider the equations of Krylov type in conformal geometry on closed smooth Riemannian manifolds, which can be viewed as an extension of σ _k -Yamabe equation. Moreover, we prove local gradient and 2nd-derivative estimates for solutions to these equations and establish an existence result.